Crystal structure of methyl 2-(1,3-dioxo-1H-benzo[de]isoquinolin-2(3H)-yl)acetate, C15H11NO4 - Peng Wei; Yang Jicai; Yue Yu; Deng Xin; Jiang Wujiu (Zeitschrift für Kristallographie - New Crystal Structures)
C15H11NO4, monoclinic, P21/n (no. 14), a = 8.0909(6) Å, b = 24.4463(18) Å, c = 12.6980(10) Å, β = 96.6020(10)°, V = 2494.9(3) Å3, Z = 8, R gt(F) = 0.0470, wR ref(F 2) = 0.1273, T = 296 (2) K.